A prospective survey of percutaneous injuries in dental post graduates during periodontal procedures. - Bali, Rishi; Pandit, Nymphea; Bali, Zarina; Thapar, Deepti (International Journal of Infection Control, 2012)
Abstract: Occupational exposures to blood borne pathogens can occur as a result of percutaneous injuries during periodontal procedures. Detailed attention to the pattern of injuries could help in developing improved strategies to further minimize their incidence.We surveyed 12 residents enrolled in the MDS course for one year to find out how many percutaneous injuries occurred during periodontal procedures .Survey questionnaire inquired in detail about the circumstances, site and the nature of injury. We also noted the risk status of patient and device which caused the injury.A total of 48 percutaneous injuries (7.84%) were received in 612 periodontal procedures in the 1 year survey. The injury rate was 4/year/resident and individual residents suffered from 2-7 injuries during the study. The difference in number of percutaneous injuries sustained in surgical periodontal procedures (41/265) was highly significant statistically (p<0.0001) when compared to those in non surgical interventions (7/670).Most injuries occurred from suture needle followed by Castroviejo and injection needle. There is a low probability of occupational transmission of blood borne diseases in periodontal procedures. The findings of this study could possibly contribute further in efforts to reduce the incidence of percutaneous injuries during periodontal procedures.